DIDACTIC CONDITIONS FOR CREATING PROBLEMS SITUATIONS IN THE PROCESS OF STUDYING HISTORY (Pedagogy of Higher and Secondary Education, 2007)
The problem situation is the obligatory component of scientific knowledge. The didactic conditions of création and effective functioning of the problem situations during studying History are opened in the article.